2012
DOI: 10.1097/jsa.0b013e318262e8e7
|View full text |Cite
|
Sign up to set email alerts
|

Distal Realignment (Tibial Tuberosity Transfer)

Abstract: Although tibial tuberosity (TT) transfer has for many years been the basis of many protocols for the management of patellar instability, the role of pure medial transfer in particular appears to be declining. In contrast, the greater recognition of the importance of patella alta as a predisposing factor to recurrent patellar dislocation has resulted in a resurgence in the popularity of distal TT transfer. When TT transfer is performed, the direction and amount of transfer is based on the patellar height and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(43 reference statements)
1
14
0
3
Order By: Relevance
“…18 The direction and the amount of transfer following tibial tubercle osteotomy depend on the patella height and the TTTG. 19 The patella height is best assessed using CDI, whereas the TTTG can be assessed using either a computed tomography or MRI scans. Some investigators consider MRI scan as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…18 The direction and the amount of transfer following tibial tubercle osteotomy depend on the patella height and the TTTG. 19 The patella height is best assessed using CDI, whereas the TTTG can be assessed using either a computed tomography or MRI scans. Some investigators consider MRI scan as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…3 Se han descrito m煤ltiples procedimientos de realineaci贸n distal, que incluyen osteotom铆a de la tuberosidad anterior para medializar, anteromedializar, distalizar o combinar distalizaci贸n y medializaci贸n. [4][5][6][7][8] El objetivo de estos procedimientos es la correcci贸n de la mala alineaci贸n subyacente del mecanismo extensor, que se manifiesta con un aumento de la distancia TT-TG (tuberosidad tibial-surco troclear) de la altura de la r贸tula. Si bien la restauraci贸n de la anatom铆a del aparato extensor suele arrojar resultados cl铆nicos favorables, el conjunto de t茅cnicas disponibles no est谩n exentas de complicaciones.…”
Section: Introductionunclassified
“…In addition to soft-tissue restraints, malalignment in the form of pathologic lateralization of the tibial tubercle (TT)dmeasured as the increased tibial tubercleetrochlear groove (TT-TG) distance (as measured on computed tomography scan or magnetic resonance imaging)dcan contribute to lateral patellar instability. [10][11][12] Excessive lateral positioning of the TT increases the lateral force vectors on the patella. 11 Multiple studies have reported the normal TT-TG distance to be less than 13 mm, abnormal to be greater than 15 mm, and pathologic to be greater than 20 mm.…”
mentioning
confidence: 99%
“…[10][11][12] Excessive lateral positioning of the TT increases the lateral force vectors on the patella. 11 Multiple studies have reported the normal TT-TG distance to be less than 13 mm, abnormal to be greater than 15 mm, and pathologic to be greater than 20 mm. 10,11,13,14 Although significant focus has been placed on patellofemoral instability in recent years, it was Goldthwait 15 who first described the etiology of patellofemoral instability in 1903, and he ultimately concluded that nonoperative management was not effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation